Diagnostic social de l'infection à VIH/Sida et stratégies endogènes de prévention à Gaoua, Burkina Faso - Donmozoun Télesphore Somé (Taylor & Francis Group, 2008)
Despite sensitising and prevention messages, women still remain concerned about AIDS in developing countries. How do they perceive the illness and methods of prevention? The objective of this study was to assess the social diagnosis of HIV/AIDS, and endogenous strategies developed by women from Gaoua. A qualitative approach was adopted, involving four focus group discussions with women from the Lobi, Birifor, Dioula and Dagara ethnic groups. An interview guide was developed for the discussions, which were carried out in local languages, tape recorded, transcribed verbatim and analysed in detail. Specific descriptions of HIV/AIDS related to signs/symptoms were given. These were: _Kpéré tchi_ (lose weight and die) _gbè yirè_ (twig feet) _sii dan_ (end of life) _gbè milè_ (thin feet), respectively for Lobi, Birifor, Dioula and Dagara. The major signs of AIDS mentioned were weight loss, appetite for meat, good meals, curly hair, large spots on the body, high fever, diarrhoea, and redness of lips. In relation to these signs, some endogenous strategies were developed by women to protect themselves against the illness, including "observation" and hot spiced meals for a few days for a partner who was absent for a long time, as well as early marriage for young girls. The social diagnosis of HIV/AIDS by a specific group like women demonstrates the gap between perceptions of the illness and prevention messages. This could help to understand that it is important to take account of communities' perceptions of illness in elaboration of prevention messages.